2012
DOI: 10.3347/kjp.2012.50.4.287
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Survey of Toxoplasmosis in Seoul and Jeju-do, and a Brief Review of Its Seroprevalence in Korea

Abstract: Knowledge of the prevalence of human Toxoplasma gondii infection is required in the Republic of Korea. In this study, we surveyed the seroprevalence of T. gondii infection and analyzed the risk factors associated with seropositivity among residents in 2 administrative districts; Seoul and the island of Jeju-do, which have contrasting epidemiologic characteristics. Sera and blood collected from 2,150 residents (1,114 in Seoul and 1,036 in Jeju-do) were checked for IgG antibody titers using ELISA and for the T. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 27 publications
3
20
0
Order By: Relevance
“…[2][3][4]20,21 In previous studies it was reported that seroprevalence of apparently healthy people was 8% in urban area and 11.3% in rural area in Korea. 22 Our study result is similar to the previous report.…”
Section: Discussionsupporting
confidence: 94%
“…[2][3][4]20,21 In previous studies it was reported that seroprevalence of apparently healthy people was 8% in urban area and 11.3% in rural area in Korea. 22 Our study result is similar to the previous report.…”
Section: Discussionsupporting
confidence: 94%
“…Toxoplasma gondii is an intracellular protozoan parasite that can infect warm-blooded animals, including humans. Toxoplasmosis is an important clinical disease worldwide and can lead to lymphadenitis, encephalitis, retinochoroiditis, congenital infection, and stillbirth [ 1 ]. T. gondii can cause infection via ingestion of tissue cysts or tachyzoites in raw or undercooked meat of infected animals, or ingestion of oocysts in the water or soil contaminated with feces of infected cats [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Toxoplasma encephalitis is less common in HIV-infected Koreans, because the seroprevalence of toxoplasma among Koreans is low compared with that of other countries [ 30 ]. Treatment for toxoplasma encephalitis consists of acute and chronic maintenance phases.…”
Section: Toxoplasma Encephalitismentioning
confidence: 99%